The Current Situation and Solutions to Improve the Management of Science and Technology Activities at Public Non-business Units under Vietnam Academy of Science and Technology - Khac Thanh Nam, Ninh (VNU Journal of Science: Policy and Management Studies; Vol 38 No 2DO - 10.25073/2588-1116/vnupam.4397, 2022)
Lately, many important documents on strategic orientation, systemizes and policies for science and technology development have been issued. The management of science and technology activities has been constantly changing and adapting; shown by more favorable legal environment; ensuring the rights and interests of organizations and individuals involved in science and technology activities; ensuring the decentralization, level of responsibilities among each participants in the implementation of science and technology activities. Due to the change in policy and practical development needs, the management of science and technology tasks at public non-business units under the Vietnam Academy of Science and Technology has made changes in accordance with the Law on Science and Technology in 2013 and Decree No. 60/2021/ND-CP dated June 21, 2021 of the Government stipulating the mechanism of financial autonomy for public non-business units. By understanding of the current situation and affecting factors of the management of science and technology activities at public non-business units, solutions are proposed to complete the management of such activities in accordance with the functions and tasks of public non-business units under the Vietnam Academy of Science and Technology will contribute to the improvement of the management of science and technology tasks of the country in general,  and of the Vietnam Academy of Science and Technology in particular.